1981
DOI: 10.1046/j.1537-2995.1981.21381201801.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Effects of Hydroxyethyl Starch on the Blood Coagulation System

Abstract: The literature related to the effects of hydroxyethyl starch on blood coagulation was reviewed to determine whether or not recipients are placed at risk of hemorrhage or thrombosis. Effects on coagulation observed when blood and HES were mixed in vitro were trivial and seemed related simply to dilution. HES affected coagulation in vivo in a dose-related fashion. When infused in moderate amounts (as employed in leukapheresis), HES rarely, if ever, caused overt bleeding, and only minor changes of laboratory coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
3

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 11 publications
3
39
0
3
Order By: Relevance
“…Prednisone was given orally either as a single dose (50 mg) about 12 h before leukapheresis, or in three divid ed doses (20 mg each) 15, 12 and 2 h before the procedure. suits in serious side-effects, temporary ab normalities in some blood chemistries [12,13], coagulation parameters [23], and plasma volume expansion after multiple transfu sions have been reported [12]. Recent studies have shown that a fraction of the infused HES is eliminated very slowly within the course of 1 year [13,14], generating uncer tainty about the safety of administering HES to leukapheresis donors repetitively.…”
Section: Resultsmentioning
confidence: 99%
“…Prednisone was given orally either as a single dose (50 mg) about 12 h before leukapheresis, or in three divid ed doses (20 mg each) 15, 12 and 2 h before the procedure. suits in serious side-effects, temporary ab normalities in some blood chemistries [12,13], coagulation parameters [23], and plasma volume expansion after multiple transfu sions have been reported [12]. Recent studies have shown that a fraction of the infused HES is eliminated very slowly within the course of 1 year [13,14], generating uncer tainty about the safety of administering HES to leukapheresis donors repetitively.…”
Section: Resultsmentioning
confidence: 99%
“…It has long been known that HES solutions interfere with coagulation 19 and that the effects vary according to the dose and type of solution administered. 20 Solutions with a high molecular weight and a high degree of substitution accumulate in the tissues and are responsible for more pronounced hemostatic effects.…”
Section: Colloidsmentioning
confidence: 99%
“…It has long been known that HES solutions interfere with coagulation 53 and that the effects vary according to the dose and type of solution administered. 54 Solutions with a high molecular weight and a high degree of substitution accumulate in the tissues and are responsible for more pronounced hemostatic effects.…”
Section: Crystalloids and Colloidsmentioning
confidence: 99%